Antimicrobial resistance as a super wicked problem: how do we engage the public to be part of the solution - Helen Rickard; Sam Watkin; Nicola Baldwin; Anthony De Souza; Lena Ciric; Elaine Cloutman-Green (Elsevier, 2023)
Summary: Antimicrobial resistance (AMR) is now regarded as one of the greatest global challenges of the 21st century. The complexity, urgent timeframe, and lack of clear solution to AMR have contributed to its classification as a 'super wicked problem'. Yet knowledge surveys of the general public have found that they still harbour numerous misconceptions linked to both the sources and impact of AMR. This confusion is compounded by AMR being a One Health issue, and therefore a factor in not just human health but in other industries, such as farming. This can further inhibit understanding and knowledge transfer around AMR for those without a prior knowledge base.In order to address the escalating risk that AMR presents, however, it is essential to address this knowledge gap and engage with the public to support wide scale changes in behaviour and consumer choice. The WHO now requires national action plans tackling AMR to include patient and public involvement/engagement (PPI/E) to support changing the trajectory of AMR. Despite this, little detail is available as part of strategic plans on how PPI/E should be undertaken in order to aid implementation. This paper discusses a number of approaches to support the design and delivery of PPI/E in relation to AMR, including the different social behaviour models underlying successful PPI/E strategies, and key considerations linked to specific activity types. The framework produced includes features for steps from initial planning and design through to evaluation. The aim is to help improve the ability of scientists and healthcare professionals to produce high quality AMR PPI/E.